Florida 4-H Treasurer's Manual and Record Book - Joy C. Jordan; Mary Thomas; Tiffany Browning (EDIS, 2009)
Revised! 4HGCR02, a 36-page full color manual by Joy Jordan, is 4-H club material that will help guide the newly elected treasurer (age 8 and up) in his or her duties and responsibilities. This record book will be the official financial record of a 4-H club. Published by the UF 4-H Youth Development Program, December 2009.